2005
DOI: 10.1111/j.1475-6765.2005.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerable populist right parties: No economic realignment fuelling their electoral success

Abstract: Abstract.  The two occupational groups most likely to vote for populist right parties in Western Europe in the 1990s also disagree the most over issues relating to the economic dimension of politics. The two groups were: blue‐collar workers – who support extensive state intervention in the economy – and owners of small businesses – who are against such state intervention. Proponents of economic realignment theories have held that both groups voted for the populist right because their economic preferences becam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(166 citation statements)
references
References 14 publications
6
153
1
6
Order By: Relevance
“…Rovny (2013) claims that those parties tend to deliberately 'blur' their positions on economic issues to attract broader electoral support. These parties present antagonistic economic positions and their voters hold significantly more dispersed economic views (Ivarsflaten, 2005). There might also be some variation in their positions across policy sub-areas -i.e.…”
Section: The Prr and The Economymentioning
confidence: 99%
“…Rovny (2013) claims that those parties tend to deliberately 'blur' their positions on economic issues to attract broader electoral support. These parties present antagonistic economic positions and their voters hold significantly more dispersed economic views (Ivarsflaten, 2005). There might also be some variation in their positions across policy sub-areas -i.e.…”
Section: The Prr and The Economymentioning
confidence: 99%
“…First, they could support them because they agree with these parties' main ideological messages. It has been shown that when it comes to radical right voting, the effect of someone's socioeconomic position is strongly a function of, or mediated by, attitudes toward immigration (see Ivarsflaten, 2008;Kriesi, Grande, Lachat, Dolezal, & Bornschier, 2008;Kriesi et al, 2006;Van der Brug, Fennema, & Tillie, 2000, 2005. In particular, those who experience economic difficulties are likely to have anti-immigration attitudes and in turn, and therefore, vote for a radical right party.…”
Section: Radical Parties and Radical Votingmentioning
confidence: 99%
“…In addition to these particular mediating attitudes, others might matter as well. For instance, recent research has shown that when it comes to both radical right and radical left voting, general left-right attitudes and attitudes toward European integration are important mediators (see Ivarsflaten, 2005;Ramiro, 2016;Van der Brug et al, 2000;Werts et al, 2013).…”
Section: Radical Parties and Radical Votingmentioning
confidence: 99%
“…First, researchers studied the role of attitudes towards migrants and integration (e.g. Ivarsflaten, 2005Ivarsflaten, , 2008Norris, 2005;Rydgren, 2008;Van der Brug et al, 2000) and second, studies turned to the role of euro-scepticism (e.g. Werts et al 2012).…”
Section: Introductionmentioning
confidence: 99%